A pilot study for the development of a diagnostic test for malignant hyperthermia : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biochemistry at Massey University - Kerr, Robin Gillian (Massey University, 1986)
The only definitive diagnostic test for Malignant Hyperthermia, a genetic disease that effects skeletal muscle, is the caffeine-contracture test. Alternative tests are being sought since this test is not totally satisfactory. It requires muscle biopsy, an invasive procedure and often produces results difficult to interpret. A test that could be used for wide spread screening of all patients about to undergo an operation would reduce the incidence of unexpected Malignant Hyperthermic episodes induced by anaesthetics, the most common cause of an episode. In this project the effect of mild stress induction on skeletal muscle, ischaemia produced by a tourniquet is studied. The tourniquet effect on a sample of five pre-diagnosed Malignant Hyperthermia susceptible subjects is compared to the effect on a sample of twelve normal subjects. The effect was determined by the measurment of serum metabolites before and after tourniquet application. The variables measured were creatine kinase, lactate dehydrogenase, AMP deaminase, total solids, total protein, potassium, osmolality, inorganic pyrophosphatase, creatine and erythrocyte pyrophosphatase. Between the two groups AMP-deaminase, creatine and osmolality showed no difference in response to tourniquet application. Inorganic pyrophosphate rose in the Malignant Hyperthermia group after tourniquet application but remained unaltered in the normal groups. All other Malignant Hyperthermia variables moved in a negative direction with respect to the normal levels. That is if the normal metabolites level rose the Malignant hyperthermia metabolites stayed the same, or if the normal levels stayed the same the MH levels dropped. A measurement of resting metabolite levels showed Creatine kinase was higher in the MH subjects compared to the normal subjects levels but creatine and pyrophosphatase were lower in the MH subjects. These differences may form the basis of a diagnostic test.
Keywords: Malignant hyperthermia